(untitled) (Czech Journal of International Relations, 1966)
In recent years, the question of whether our Earth is capable of supporting an ever-increasing population has come to the fore as a central problem for the future of humanity. Economists, politicians, agronomists examine, each from their own point of view, how to cope with the so-called "Population explosion", with "unprecedented dynamics" of world population growth, with "overpopulation" of our globe, with "hunger that threatens all humanity". Opinions on the solution to this problem vary: they range from the recreational and anti-humane return of the American CH. Gotta, according to which the so-called "Inferior" societies, races and nations should not only be given no help, but their demise should be hastened - by limiting the birth rate to complete sterilization, especially in the so-called Overcrowded areas - up to proposals for economically developed countries to substantially increase their efforts in food production and contribute much more effectively than before to covering the food deficit in those developing countries where the population pressure is strongest.